Format and Order Revealing Encryption - Paiva, Rui David Teixeira (2018)
As more and more cloud services emerge so does the need for new methods for securing the data these services consume, especially since data leaks have become the norm rather than the exception. Since most cloud services require some kind of access to our private data in order to perform searches and provide services, new ways of securing our data in the cloud is needed. This dissertation examines the current state of the cryptographic world in order to try to and understand and resume what solutions currently exist for this particular type of problem. This work is motivated by a particular problem of data delegation to a cloud infrastructure. This problem involves the protection of sensitive data whilst it’s analysed by a third party. While there is no simple approach to solve this particular problem, this dissertation discusses three main approaches to tackle this problem. One approach attempts to define a new cryptographic scheme with a leakage profile that would allow a third party to only have access to some information of the plaintext but, at the same time, keep the plaintext safe from attackers. Another approach attempts to use already existing cryptographic schemes, such as, Format Preserving Encryption and Order Revealing Encryption to solve this particular problem. A final approach tries to solve this problem by utilising cryptographic tools, such as hash-functions and hash-based message authentication codes. An extended study was also conducted in many cryptographic schemes, both current and old cryptographic schemes. This study allowed for a better view of the cryptographic world and how these schemes could help us achieve a solution. For this dissertation, a prototype was also implemented of some recent cryptographic schemes. These prototype implementations allowed for a deeper understanding of how these schemes work and also allowed us to conduct some experiments while trying to combine two cryptographic schemes. The results of this dissertation show that that trying to solve a problem via creating a new cryptographic scheme is not an easy feat especially when one wants to define correctly the strict security requirements and also the work needed to understand the mathematical workings of similar schemes. Lastly we conclude that solving the problem with the help of already existing tools may be the easiest solution, but, it may also only work for a specific scenario and hence is of no use in other similar situations. A solution to the particular problem studied in this thesis is also presented at the end of this dissertation, although, it only applies to this specific problem and does not solve the more general problem of privacy of data delegation to the cloud.